Step-by-step explanation:
[tex] \sin( \frac{ \alpha }{2} ) = \sqrt{ \frac{1 - \cos( \alpha ) }{2} } [/tex]
[tex] \cos( \frac{ \alpha }{2} ) = \sqrt{ \frac{1 + \cos( \alpha ) }{2} } [/tex]
Find cos using Pythagorean theorem.
[tex]( \sin( \alpha ) ) {}^{2} + ( \cos( \alpha ) ) {}^{2} = 1[/tex]
[tex]( \frac{11}{19} ) { }^{2} + ( \cos( \alpha ) ) {}^{2} = 1[/tex]
[tex]( \frac{121}{281} ) + ( \cos( \alpha ) ) {}^{2} = 1[/tex]
[tex]( \cos( \alpha ) ) {}^{2} = \frac{160}{281} [/tex]
[tex] \cos( \alpha ) = \frac{4 \sqrt{10} }{19} [/tex]
Now, we use the formula
[tex] \sin( \frac{ \alpha }{2} ) = \sqrt{ \frac{1 - \frac{4 \sqrt{10} }{19} }{2} } [/tex]
[tex] \sin( \frac{ \alpha }{2} ) = \sqrt{ \frac{ \frac{19 - 4 \sqrt{10} }{19} }{2} } [/tex]
[tex] \sin( \frac{ \alpha }{2} ) = \sqrt{ \frac{19 - 4 \sqrt{10} }{38} } [/tex]
[tex] \cos( \frac{ \alpha }{2} ) = \sqrt{ \frac{1 + \cos( \alpha ) }{2} } [/tex]
[tex] \cos( \frac{ \alpha }{2} ) = \sqrt{ \frac{19 + 4 \sqrt{10} }{38} } [/tex]